2002
DOI: 10.1002/acp.815
|View full text |Cite
|
Sign up to set email alerts
|

Memory for autobiographical facts and events: a comparison of women reporting childhood sexual abuse and non‐abused controls

Abstract: Although there is evidence that many adult survivors of childhood sexual abuse (CSA) have a period when they forget their abuse, existing research is equivocal about whether such individuals show other autobiographical memory impairments. The present study addressed some of the sampling and measurement problems apparent in previous studies and compared 74 women reporting a history of CSA with 60 non-abused controls on their ability to recall facts and events from childhood. The results showed that the CSA grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…We therefore utilized a cued-recall procedure, in which participants had to indicate whether and how well they remembered each of 11 specific events (cf., e.g. Auriat, 1993;Hunter & Andrews, 2002;Rubin, Rahhal, & Poon, 1998;White, 2002;see Neisser & Libby, 2000, for an overview of 'targeted recall'). The events included eight personal and three public events (see Appendix).…”
Section: Am Questionnairementioning
confidence: 99%
“…We therefore utilized a cued-recall procedure, in which participants had to indicate whether and how well they remembered each of 11 specific events (cf., e.g. Auriat, 1993;Hunter & Andrews, 2002;Rubin, Rahhal, & Poon, 1998;White, 2002;see Neisser & Libby, 2000, for an overview of 'targeted recall'). The events included eight personal and three public events (see Appendix).…”
Section: Am Questionnairementioning
confidence: 99%
“…For instance, stress related cortisol elevations have been shown to have a negative effect on declarative memory (Elzinga & Bremner, 2002). Studies examining traumatized individuals (Moradi, Doost, Taghavi, Yule, & Dagleish, 1999), including those with early abuse experiences and who have been diagnosed with stress-related mental disorders (Bremner et al, 2003;Elzinga & Bremner, 2002;Kuyken & Brewin, 1995), have found maltreatment to be associated with a wide variety of cognitive difficulties such as reduced working memory performance (Matthias, Nater, Lin, Capuron & Reeves, 2010), difficulties in reporting autobiographical facts from childhood (Hunter & Andrews, 2002;Valentino, Toth, & Cicchetti, 2009; but see Greenhoot, Bunnell, Curtis, & Beyer, 2008), and increased memory errors in facial recognition tasks (Pollak, Cicchetti, Hornung, & Reed, 2000). This suggests that there may be some aspects of maltreated children's memory that may be more vulnerable than non-maltreated children's memory to influences that distort what is being remembered (see also Beers & De Bellis, 2002;Carrion, Haas, Garrett, Song, & Reiss, 2010;Cicchetti, Rogosch, Howe, & Toth, 2010;Kirk-Smith, Henry, & Messer, 2014).…”
mentioning
confidence: 99%
“…Scientific investigations of the possible effects of child maltreatment on autobiographical memory reveal deficits as well as advantages. Evidence of a detrimental effect is drawn from research in which adult survivors of child abuse self-report or exhibit deficits in episodic autobiographical memory (autobiographical memories involving mental travel back in time; e.g., Edwards, Fivush, Anda, Felitti, & Nordenberg, 2001) and semantic autobiographical memory (autobiographical memory for facts such as past addresses; e.g., Hunter & Andrews, 2002; Meesters, Merckelbach, Muris, & Wessel, 2000; Stokes, Dritschel, & Bekerian, 2008) concerning childhood experiences. In contrast, research has also shown that both adult and child victims of child maltreatment can have accurate and detailed memories for events related to their abuse experiences.…”
mentioning
confidence: 99%